The Effects of Urban Spatial Structure on Travel Demand in the United States - Bento, Antonio M.; Cropper, Maureen L.; Mobarak, Ahmed Mushfiq; Vinha, Katja (The Review of Economics and Statistics, 2005)
We examine the effects of urban form and public transit supply on the commute mode choices and annual vehicle miles traveled (VMTs) of households living in 114 urban areas in 1990. The probability of driving to work is lower the higher are population centrality and rail miles supplied and the lower is road density. Population centrality, jobs-housing balance, city shape, and road density have a significant effect on annual household VMTs. Although individual elasticities are small absolute values (≤0.10), moving sample households from a city with the characteristics of Atlanta to a city with the characteristics of Boston reduces annual VMTs by 25%.